2004
DOI: 10.1136/tc.2004.007484
|View full text |Cite
|
Sign up to set email alerts
|

Hedging their bets: tobacco and gambling industries work against smoke-free policies

Abstract: Objective:To describe and understand the relationship between the tobacco and gambling industries in connection to their collaborative efforts to prevent smoke-free casinos and gambling facilities and fight smoke-free policies generally.Methods:Analysis of tobacco industry documents available online (accessed between February and December 2003).Results:The tobacco industry has worked to convince the gambling industry to fight against smoke-free environments. Representatives of the gambling industry with ties t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Tobacco companies, hospitality coalitions, restaurant associations, gambling organizations, licensed beverage associations, and smokers' rights groups often campaign actively against smoke-free laws (Dearlove, Bialous & Glantz, 2002;Mandel & Glantz, 2004;Tsoukalas & Glantz, 2003). These groups deliberately promote state preemption laws, indoor ventilation alternatives, and claim that business owners will lose money if comprehensive smoke-free policies are enacted (Americans for Nonsmokers ' Rights, 2005).…”
Section: Specific Strategies To Mobilize a Community For Smoke-free Pmentioning
confidence: 96%
“…Tobacco companies, hospitality coalitions, restaurant associations, gambling organizations, licensed beverage associations, and smokers' rights groups often campaign actively against smoke-free laws (Dearlove, Bialous & Glantz, 2002;Mandel & Glantz, 2004;Tsoukalas & Glantz, 2003). These groups deliberately promote state preemption laws, indoor ventilation alternatives, and claim that business owners will lose money if comprehensive smoke-free policies are enacted (Americans for Nonsmokers ' Rights, 2005).…”
Section: Specific Strategies To Mobilize a Community For Smoke-free Pmentioning
confidence: 96%
“…Tobacco industry documents have shown that the tobacco industry has lobbied against smoke-free policies in casinos by trying to convince casino owners that smoke-free policies will decrease their revenue and that ventilation systems are an adequate alternative [12]. These activities by the tobacco industry also may convince the owners of American-Indian casinos not to institute smoke-free policies.…”
Section: Discussionmentioning
confidence: 91%
“…Worldwide, the industry has secretly hired consultants, sponsored symposia, financed research, and engaged in lobbying in order to fuel the controversy on the relationship between SHS and disease (Barnoya & Glantz, 2002;Hammond & Assunta, 2003;Muggli et al, 2003;Repace, 2004a). In recent years, especially in the United States, the industry has shifted the focus to economic claims that smoke-free environments are disastrous for the hospitality industry, investing millions of dollars in restaurant associations (Dearlove et al, 2002) and in the gaming industry (Mandel & Glantz, 2004). These claims continue to be pressed vigorously to oppose legislation, despite the fact that all high-quality independently funded and peer-reviewed research regarding the effects of smoke-free policies on the hospitality industry has consistently shown no effect or a positive effect on revenue (Hahn, 2010;Scollo, Lal, Hyland, & Glantz, 2003).…”
Section: The Tobacco Industry and Smoke-free Environmentsmentioning
confidence: 99%